The effects of whole-body vibration training on decuple jump performance in handball athletes - Lee, A. J. Y.; Chang, H. K.; Liang, L. C.; Lin, W. H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
To evaluate the effects of whole-body vibration training (WBVT) on decuple jump performance in handball athletes. Sixteen collegiate Level I handball athletes volunteered and divided equally as control group and experimental group (EG). All athletes underwent the same handball specific training, but the EG received additional WBVT (amplitude: 2 mm, frequency: 20 - 40 Hz) three time per week for eight weeks. The decuple jump (DJ) performance was evaluated by the total distance covered in ten single leg long jumps. Single factor ANCOVA was used to examine the differences in each parameter between the groups after training with the pretest values as a covariate. The statistic significance was set at p < .05. Results showed that after 8 weeks WBVT, the EG had significantly improved the total distance of DJ (25.03 ± 1.83 m vs. 26.26 ± 1.65 m, F = 5.45, p < .05). It is concluded that 8 weeks of additional WBVT could improve the decuple jump performance in handball athletes.